(E)-2-[4-(Diethylamino)styryl]-1-methylpyridinium benzenesulfonate monohydrate - Fun, Hoong-Kun (International Union of Crystallography, 2011)
The asymmetric unit of the title compound, C(18)H(23)N(2) (+)·C(6)H(5)O(3)S(−)·H(2)O, comprises a 2-[4-(diethylamino)styryl]-1-methylpyridinium cation, a benzenesulfonate anion and a solvent water molecule. One ethyl substituent of the diethylamino group of the cation is disordered over two positions in a 0.73789 (9):0.26211 (9) ratio. The cation exists in the E configuration with respect to the C=C bond and the π-conjugated system is essentially planar with a dihedral angle of 0.82 (10)° between the pyridinium and benzene rings. The cation and anion are almost orthogonal with a dihedral angle of 86.71 (10)° between the π-conjugated system of the cation and benzene ring of the anion. In the crystal, molecules are arranged into chains along [001] and adjacent chains are linked by weak C—H⋯O interactions. The crystal is further stablilized by O—H⋯O hydrogen bonds and weak C—H⋯π interactions.